Pharmacological effects of Bufei Jianpi granule on chronic obstructive pulmonary disease and its metabolism in rats - Yang, Xin-Xin; Wang, Shuai; Cui, Lin-Lin; Li, Tian-Jiao; Bai, Gang; Bao, Yong-Rui; Meng, Xian-Sheng (Frontiers in Pharmacology, 2022)
Chronic obstructive pulmonary disease (COPD) ranked as the third leading cause of death in the world, seriously endangering human health. At present, the pathogenesis of COPD is complex and unclear, most of the drugs used are to alleviate and improve symptoms, they cannot achieve the purpose of eradicating the disease. Bufei Jianpi Granule (BJG) is a Chinese medicine developed by the Affiliated Hospital of Henan University of Traditional Chinese medicine treating COPD. This study concentrates on the pharmacological effects of BJG on COPD and its metabolism in rats, aiming to provide a scientific basis for developing BJG against COPD. 72 Sprague-Dawley (SD) rats were divided into blank group, model group, positive control group and BJG groups (2.36, 1.18, 0.59 g/kg). Except for the blank group, rats in other groups was established a COPD model by Lipopolysaccharide (LPS) combined with smoking for 6 weeks. After another 6 weeks of treatment, the therapeutic effect of BJG on COPD rats were evaluated. In BJG (2.36 g/kg) group, cough of rats was significantly relieved, the body weight was close to blank group. Compared with the mortality of 16.7% in model group, no death arised in BJG (2.36 g/kg) and (1.18 g/kg) groups. The lung tissue damage in BJG groups was less than that in COPD group. Compared with the model group, MV, PIF, PEF and EF50 in BJG groups were observably increased as dose dependent manner, while sRaw, Raw and FRC were obviously decreased. And content of IL-6, IL-8, TNF-α, PGE2, MMP-9 and NO in serum and BALF was lowered dramatically in all BJG groups. All indicators presents obvious dose-effect relationship. On this basis, UPLC-QTOF-MS/MS technology was used to analyze characteristic metabolites in rats under physiological and pathological conditions. A total of 17 prototype and 7 metabolite components were detected, the concentration of most components increased in COPD pathologic state. It is suggested that BJG has pharamcolgical effect for the treatment of COPD, the absorption and metabolism of chemical components of BJG in rats exhibited significant difference under the physiological and pathological conditions.